THE RIGHTS OF THE FAMILIES OF MISSING PERSONS: GOING BEYOND INTERNATIONAL HUMANITARIAN LAW - Baranowska, Grażyna (Israel Law Review, 2022)
The main aim of the article is to test how states implement international humanitarian law (IHL) with regard to the families of missing persons. The article shows relevant IHL shortcomings and compares them with rules applicable in cases of enforced disappearance. The national legislation collected in the section titled ‘The Missing and Their Families’ of the National Implementation Database of the International Committee of the Red Cross is then examined. The analysis addresses three core questions that are particularly relevant for families of missing persons: (1) Who is considered a missing person under each law? Approaching this question allows the testing of whether states follow the understanding of ‘missing persons’ under IHL treaty law. The second and third questions address two issues that are crucial for families of missing persons that are not addressed in IHL: (2) How is the legal status of the missing person regulated? (3) Are family members provided with measures of reparation and/or assistance? This approach reveals that states rarely apply the IHL understanding of ‘missing persons’ and predominantly exceed IHL by addressing some of the identified shortcomings. It further shows that states provide families of missing persons either with reparation measures – in cases of human rights violations – or, less often, with measures of assistance in post-conflict situations.
CRIS-Team Scopus Importer:2024-08-12
Keywords: enforced disappearance; families of missing persons; IHL implementation; legal status of missing persons; measures of assistance; missing persons; reparation; socio-economic needs